SISTEM INFORMASI TUGAS AKHIR BERBASIS WEB UNIVERSITAS SAHID SURAKARTA - Setiyawan, Ade; Retnoningsih, Dwi; Anwariningsih, Sri Huning (2086-4221, 2012)
Information Systems of Final Project in Sahid University of Surakarta  still using manual systems, where the filing of the title is still using a paper form, the student must immediately meet the Study Program Chairman and academic advisor for raising titles  and  information about  any  title  that  has been received  is still not  transparent. Information  about anyone who  has  graduated  and  who  will  graduate  and  the graduation schedule is not yet maximal. Information Systems of Final Project which can be accessed quickly  students are needed  so that  students can obtain  information more quickly and accurately about the End Task. The method  used  in the manufacture of  this  Information Systems of Final Project  using  structured programming.  Testing  the system  in this study  using the method of Mc Call, using  five  factors: portability, reliability, maintainability, usability and compability. Mc Call method was chosen because it is easy to use and powerful tool to measure software quality. Information Systems of Final Project  based web  is the right step  to  provide information about the final project that can be accessed efficiently by the students who took the  Final.  This system  can also be  used  as a means  to  consult a  counselor  for students enrolled following the End Task. Information Systems of Final Project which is expected to be web-based facilities that support the process of final project at the Sahid University of Surakarta. Having measured using the method of Mc Call, the total value of  the quality of  this  system  is  (77,8  %)).  The value  of measuring  the quality of  the systems have been able to determine that the system can be used in Sahid University of Surakarta.